Moderating Effect of Board Gender Diversity on Institutional Investor and Agency Cost - Nuraina, Elva; Haryanto, Sendy Dwi; Harwida, Gita Arasy (Faculty of Economics, Universitas Sriwijaya, 2024)
This study examines the influence of institutional investors on agency costs and investigates board gender diversity's moderating role in this relationship among Indonesian listed companies from 2018-2022. Using a sample of 550 firm-year observations, we find that institutional investors significantly reduce agency costs through enhanced monitoring mechanisms. Our results demonstrate that board gender diversity strengthens institutional investors' effectiveness in mitigating agency costs, suggesting that gender-diverse boards complement institutional monitoring. Specifically, the interaction between institutional ownership and board gender diversity leads to lower agency costs, supporting recent regulatory initiatives promoting gender diversity in corporate leadership. These findings contribute to corporate governance literature by identifying how board composition influences institutional investors' monitoring effectiveness and provide practical implications for policymakers and firms seeking to optimize governance structures. Our study extends agency theory by demonstrating how gender diversity in board composition enhances monitoring quality and reduces principal-agent conflicts in emerging market contexts.